(untitled) (Swiss Medical Weekly, 2014)
Migration of health professionals is one of the drivers of vast inequalities in access to healthcare, as medical graduates tend to move away from both poorer countries and rural areas. One of the central ethical problems raised in attempting to alleviate these inequalities is the tension between the healthcare needs of under-served patients and the rights of medical graduates to choose their place of work and specialty. If medical graduates had greater motivation to work in under-served rural areas, this tension would decrease accordingly. Medical schools have a duty to avoid eroding existing motivation for such training and practice. This duty has practical implications. Medical students’ motivation regarding their choice of specialty changes during medical training, turning them away from choices such as primary care and rural practice towards more highly specialised, more hospital based specialties. Although students may be victims of a number of biases in the initial assessment, this is unlikely to be the whole story. Students’ priorities are likely to change based on their admiration for specialist role models and the visibility of the financial and non-financial rewards attached to these specialties. Students may also have a false expectation upon admission that they will be proficient in rural medicine on graduation, and change their mind once they realise the limits of their skills in that area. Although the measures required to reverse this effect currently lack a solid evidence base, they are plausible and supported by the available data.